Unexpected loc.sg. -â in High Latvian - Kalniņš, Aigars (Baltistica, 2024)
This paper investigates ā-stem locative singular endings in the High Latvian dialects. It is shown that the phenomenon of labialization of inherited *ā largely rebuts the traditional comparison of Low Latvian loc. sg. -â with High Latvian -â because in most dialects we in fact expect -ô, ‑ôa or ‑uô instead. Following an alternative line of thought, this “unexpected” loc. sg. -â is rather identified with loc. sg. -ai and a new sound law is proposed, according to which word-final, unaccented *-aî is widely monophthongized to -â. Apart from the locative singular the effects hereof are also seen in navâ (< *navaî) ‘(there) is not’ and perhaps also visâ (< *visaî) ‘particularly; entirely.’ The etymological identity of LLv. -ai and HLv. -â is also suggested by the fact that -ai is attested right along the isogloss for unexpected -â—a distribution that is very similar to that of -ai and its cognates -ei, -ē and -ȩ etc. in Kurzeme. As a result, loc. sg. *-ai appears to be significantly more widespread than previously assumed, while the isogloss for *-â is accordingly narrowed so that it only includes LLv. -â; HLv. -ô, -ôa, -uô, etc.; and at least part of the High Latvian dialects that attest -â but have no regular labialization.